2021
DOI: 10.1103/physrevlett.127.180502
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Programmable Gaussian Boson Sampling Using Stimulated Squeezed Light

Abstract: We report phase-programmable Gaussian boson sampling (GBS) which produces up to 113 photon detection events out of a 144-mode photonic circuit. A new high-brightness and scalable quantum light source is developed, exploring the idea of stimulated emission of squeezed photons, which has simultaneously near-unity purity and efficiency. This GBS is programmable by tuning the phase of the input squeezed states. The obtained samples are efficiently validated by inferring from computationally friendly subsystems, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
210
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(228 citation statements)
references
References 74 publications
2
210
0
1
Order By: Relevance
“…Conventional supercomputers, albeit versatile and remarkably reliable, seem to be outpaced by ever-increasing demand for computational power when developing new drugs [ 1 ], modeling nanoparticles [ 2 ], or assessing problems in materials science [ 3 ] and nuclear physics [ 4 , 5 ]. In contrast to the well-established conventional technologies, quantum computers are expected to provide exponentially growing computational power thanks to the their use of quantum effects [ 6 , 7 ], and the first indications of so-called quantum advantage/supremacy have already been demonstrated [ 8 , 9 , 10 ]. Unfortunately, the current capabilities of quantum computers are still rather limited by numerous methodological issues, a lack of suitable software tools, challenges when physically realizing quantum circuits, noise, which reduces their reliability, as well as a very low number of quantum platforms available for users.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional supercomputers, albeit versatile and remarkably reliable, seem to be outpaced by ever-increasing demand for computational power when developing new drugs [ 1 ], modeling nanoparticles [ 2 ], or assessing problems in materials science [ 3 ] and nuclear physics [ 4 , 5 ]. In contrast to the well-established conventional technologies, quantum computers are expected to provide exponentially growing computational power thanks to the their use of quantum effects [ 6 , 7 ], and the first indications of so-called quantum advantage/supremacy have already been demonstrated [ 8 , 9 , 10 ]. Unfortunately, the current capabilities of quantum computers are still rather limited by numerous methodological issues, a lack of suitable software tools, challenges when physically realizing quantum circuits, noise, which reduces their reliability, as well as a very low number of quantum platforms available for users.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond tests of quantum computational complexity using photons [3,27], optical approaches to universal measurement-based quantum computation rely on the generation of small entangled states that can be combined to build up a cluster resource state [28,29]. The effect of photon distinguishability on fault tolerant schemes has been investigated [30], but a more general treatment also including effects of photon impurity -and routes to protect against such errors -will become crucial as the scale of optical quantum technologies continues to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the computing experiments and data analysis have shown that a 200-second job of Gaussian Boson sampling on Jiuzhang would require 0.6 billon years for the fastest supercomputer available at the time to finish. It was reported in Zhong et al, 2021 that the second generation of Jiuzhang was built with up to 113 qubits and enhanced performance.…”
Section: Quantum Factoring Algorithms and Cryptographymentioning
confidence: 99%